2004
DOI: 10.1038/sj.bjc.6601870
|View full text |Cite
|
Sign up to set email alerts
|

Use of neoadjuvant chemotherapy prior to radical hysterectomy in cervical cancer: monitoring tumour shrinkage and molecular profile on magnetic resonance and assessment of 3-year outcome

Abstract: The objective of this study is to assess tumour response to neoadjuvant chemotherapy prior to radical hysterectomy in cervical cancer using magnetic resonance (MR) to monitor tumour volume and changes in molecular profile and to compare the survival to that of a control group. Eligibility included Stage Ib -IIb previously untreated cervical tumours 410 cm 3 . Neoadjuvant chemotherapy in 22 patients (methotrexate 300 mg m À2 (with folinic acid rescue), bleomycin 30 mg m À2 , cisplatin 60 mg m À2 ) was repeated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(19 citation statements)
references
References 28 publications
0
19
0
Order By: Relevance
“…105 Some cancers, eg, cervical cancer, did not exhibit a change in the tCho signal following neoadjuvant therapy and subsequent surgical resection of the tumors. 106 However, these cervical cancers displayed a reduced tumor volume along with decreased triglyceride signal, without any difference in patient survival with or without neoadjuvant therapy, and there was no survival advantage associated with the reduced tumor volume or decreased triglycerides. 106 …”
Section: H Mrs Monitoring Of Cancer Therapy: Clinical and Preclinicamentioning
confidence: 87%
See 1 more Smart Citation
“…105 Some cancers, eg, cervical cancer, did not exhibit a change in the tCho signal following neoadjuvant therapy and subsequent surgical resection of the tumors. 106 However, these cervical cancers displayed a reduced tumor volume along with decreased triglyceride signal, without any difference in patient survival with or without neoadjuvant therapy, and there was no survival advantage associated with the reduced tumor volume or decreased triglycerides. 106 …”
Section: H Mrs Monitoring Of Cancer Therapy: Clinical and Preclinicamentioning
confidence: 87%
“…106 However, these cervical cancers displayed a reduced tumor volume along with decreased triglyceride signal, without any difference in patient survival with or without neoadjuvant therapy, and there was no survival advantage associated with the reduced tumor volume or decreased triglycerides. 106 …”
Section: H Mrs Monitoring Of Cancer Therapy: Clinical and Preclinicamentioning
confidence: 87%
“…6 This particular study used MR imaging to monitor tumour volume and MRS to detect changes in molecular profile to assess response and compare the survival with that of a control group. A total of 23 women treated with either radical surgery or chemoradiotherapy treated over the same time period made up the nonrandomised control group.…”
Section: Discussionmentioning
confidence: 99%
“…Some scholars believe that neoadjuvant chemotherapy in combination with surgery can enhance long-term survival of the Stage IB2 and IIB patients [14,15] . Others have reported that neoadjuvant chemotherapy can markedly reduce the tumor diameter, but has little significant effect on improvement of the overall survivals and disease-free survivals [16,17] . Certainly, the above-mentioned therapeutic approach remains to be validated by prospective clinical trials.…”
Section: Discussionmentioning
confidence: 99%